PENGARUH PENGGUNAAN MOBILE BANKING DAN E-COMMERCE TERHADAP PERILAKU KONSUMTIF MAHASISWA STKIP MAJENANG TAHUN 2023 - Eka Putri Purwanti; Almunawaroh, Tri; Yogi Nurfauzi (HATTA : Jurnal Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
Based on observations, most students at STKIP Majenang use m-banking because of the factors of speed, convenience, and convenience in transactions. Because of these factors, they choose to use e-commerce for shopping to meet their needs. However, not everyone can control themselves when they see a variety of interesting items, so they often khilaf and buy goods outside of need. This study aims to determine the influence of the use of mobile banking and e-commerce on the consumptive behavior of STKIP Majenang students, both partially and simultaneously. This study uses a quantitative type of research approach. The population in this study is all students of STKIP Majenang who have mobile banking and e-commerce applications, amounting to 79 people. Sampling in this study used saturated samples, where all populations were sampled. Data collection techniques in this study are observation, interviews, and questionnaire distribution. Multiple regression tests showed significance values of 0.285 > 0.05 and calculated t values of 1.077 < t values of tables of 1.991. The results of the hypothesis test (partial test), where the significance value is 0.03 < 0.05 and the calculated t value is 3.045 > t table 1.991. In the calculation of the correlation coefficient obtained, the F count is 7.176 > F table is 3.12, and the significance level is 0.001 < 0.05 The results showed that there was no influence between mobile banking and student consumptive behavior. However, there is a positive and significant influence between e-commerce and consumptive behavior. And there is a significant influence between mobile banking and e-commerce on student consumptive behavior